2018
DOI: 10.1590/18069657rbcs20170342
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and Spatial Variability of Rare Earth Elements in Soils under Different Geological and Climate Patterns of the Brazilian Northeast

Abstract: Growth in the agricultural and industrial sectors has increased the demand for rare earth elements (REEs) in the production of technological devices and fertilizers. Thus, the accumulation of these elements in the soil has become an environmental concern. Here, we aim to determine the natural contents of REEs in soils derived from different parent materials and under climatic conditions ranging from humid to semi-arid. We then evaluate the influence of major elements and soil properties on the geochemistry of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…The lowest levels were observed in Entisols Fluvents, which reflect their composition known to be enriched in quartz sediments. These results are in agreement with those shown by Silva et al (2018a) and Alfaro et al (2018), who observed that even under humid tropical patterns, the parent material played an important role in the geochemistry of the REEs. Soils derived from igneous rocks tend to have the highest concentrations of the REEs (Hu et al, 2006).…”
Section: Natural Content Of Rees In Soilssupporting
confidence: 93%
See 4 more Smart Citations
“…The lowest levels were observed in Entisols Fluvents, which reflect their composition known to be enriched in quartz sediments. These results are in agreement with those shown by Silva et al (2018a) and Alfaro et al (2018), who observed that even under humid tropical patterns, the parent material played an important role in the geochemistry of the REEs. Soils derived from igneous rocks tend to have the highest concentrations of the REEs (Hu et al, 2006).…”
Section: Natural Content Of Rees In Soilssupporting
confidence: 93%
“…The average background concentrations of REEs in tropical soils of Gurguéia watershed followed the order (mg kg -1 ): Ce (14.01) > Nd (6.19) > La (5.52) > Pr (2.51) > Sm (1.45) > Gd (0.93) > Dy (0.63) > Er (0.42) > Yb (0.39) > Tb (0.28) > Eu (0.26) > Lu (0.20) (Table 1). These values were much lower than those found in soils from Brazil (Silva et al, 2016;Paye et al, 2016;Silva et al, 2018a), China (Wei et al, 1991), Japan (Yoshida et al, 1998), Cuba (Alfaro et al, 2018) and Europe (Sadeghi et al, 2013) (Table 1). The lowest concentrations of LREEs and HREEs in the soils from Gurguéia watershed are governed by parent material, with a predominance of soils originating from quartz sandstones.…”
Section: Natural Content Of Rees In Soilsmentioning
confidence: 53%
See 3 more Smart Citations